2001
DOI: 10.1093/nar/29.5.1238
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among group II intron ORFs

Abstract: Group II introns are widely believed to have been ancestors of spliceosomal introns, yet little is known about their own evolutionary history. In order to address the evolution of mobile group II introns, we have compiled 71 open reading frames (ORFs) related to group II intron reverse transcriptases and subjected their derived amino acid sequences to phylogenetic analysis. The phylogenetic tree was rooted with reverse transcriptases (RTs) of non-long terminal repeat retroelements, and the inferred phylogeny r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
236
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(241 citation statements)
references
References 45 publications
5
236
0
Order By: Relevance
“…Phylogenetic analysis of the most frequently observed intron S1396, a group II intron, revealed that it was probably acquired both vertically and horizontally within the family. This feature is well known among group II introns (46)(47)(48)(49). Comparative sequence analysis of intron S1396 generally reflects the phylogeny suggested by 16S rRNA sequence analysis at species level (Table S1 and Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Phylogenetic analysis of the most frequently observed intron S1396, a group II intron, revealed that it was probably acquired both vertically and horizontally within the family. This feature is well known among group II introns (46)(47)(48)(49). Comparative sequence analysis of intron S1396 generally reflects the phylogeny suggested by 16S rRNA sequence analysis at species level (Table S1 and Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Full sequences of E.c.I1 and E.c.I3 were obtained by PCR amplification of the introns based on predicted flanking exon sequences and host strains (Ferat et al+, 1994), followed by cloning and sequencing (see Material and Methods)+ Based on the completed sequences, all five introns can be described+ E.c.I1, E.c.I2, and E.c.I3 are related to each other and belong to the previously defined subclass "bacterial class D+" (Intron subclasses are based on phylogenetic groupings of the intron-encoded ORFs, but each subclass also has a distinct intron secondary structure; Toor et al+, 2001;Zimmerly et al+, 2001+) Typical of bacterial class D, the introns are IIB-like in RNA structure (Fig+ 1A,B), and the ORFs lack a Zn domain+ Although the Zn domain is required for mobility of Lactococcus Ll+ltrB (Cousineau et al+, 1998), many bacterial introns do not contain Zn domains and at least one of these is efficiently mobile nevertheless (Martinez-Abarca & Toro, 2000a)+ E.c.I1 and E.c.I2 are 67% identical in DNA sequence, whereas E.c.I3 is much less related, with 44% identity to E.c.I2 over its ORF+ E.c.I1 sequence from ECOR43 has a stop codon in RT domain 6 and a frame shift in domain X, suggesting loss of mobility and splicing functions+ E.c.I1 and E.c.I2 are inserted into an ISEc1 element, which is itself contained within an Recombination hot spot (Rhs) element (Ferat et al+, 1994)+ ISEc1 was previously called an H-repeat, but has been renamed ISEc1 because of its resemblance to IS elements (Mahillon & Chandler, 1998)+ The Rhs element is an ;6-kb DNA found in five copies in the sequenced K-12 genome+ There are at least eight varieties of Rhs elements (A-H), whose core sequences are .70% identical, but which differ in organization and lengths of spacer elements (Zhao et al+, 1993;Bachellier et al+, 1996;Wang et al+, 1998)+ At the 39 terminus of most Rhs elements is an ISEc1 copy, which is flanked by 11 bp inverted repeats+ E.c.I1 is inserted 4 bp after the upstream inverted repeat, whereas E.c.I2 is inserted near the 39 end of the ISEc1 ORF+ E.c.I3 is also located in an IS element, IS679+ E.c.I4 belongs to the subclass "bacterial class A," and its only other relative is the essentially identical intron in the closely related bacterium Shigella (99+4% identity)+ A possible secondary structure is shown in Figure 1C+ According to information in the databases, the intron has two homing sites in IS629 and IS911 elements, which share only 60% identity (Fig+ 2D)+ (We use the term "homing site" to denote the insertion site for all five introns in this study+ Although homing has not been experimentally demonstrated, it is suggested because the introns are repeatedly found within the same flanking sequences+)…”
Section: Completion Of Sequencing Of Two Introns and Description Of Amentioning
confidence: 99%
“…It has also been assigned to phylogenetic bacterial class D (17,18) on the basis of the internally encoded (ORF within DIV) reverse transcriptasematurase (intron-encoded protein (IEP)). This group II intron is excised, both in vivo and in vitro, as an intron lariat (16,19).…”
mentioning
confidence: 99%